Models of digital banks: foreign experience - Makysh , M.K. (BUKETOV BUSINESS REVIEW, 2019)
In the article innovations in banking and foreign experience of digitalization were studied. The catalyst of banking activity is considered as the main factors of development of banking innovations. The study will establish the boundaries of the digital model of banking, to determine its specific features and peculiarities of functioning, to deepen the understanding of the subjects of the banking system of modern features of the development of banking services. The presented materials can become a theoretical basis for the identification and orientation of the level of development of banking services, which contributes to the coordination of credit institutions and banking systems of the world, aimed at improving the competitiveness and efficiency of their activities in terms of the impact of digitalization processes on the transformation of banking services. The results of the study can serve as a basis for forecasting the prospects for further improvement of banking services in order to implement the systematic development of banking activities. Modern foreign studies in the field of banking indicate the continued adaptation of banking systems of the leading countries of the world to the digital model of banking services. Despite the fact that the current stage of development of both the world and the banking system is closely related to the implementation of digital transformation of customer service processes of credit institutions, little attention is paid to the study of researchers of the essence of the digital model of banking. Insufficient development of the theoretical basis of digital banking services hinders the planned and effective development of banking activities. In this regard, this article proposes a simulation of banking services in order to distribute the criteria and evaluation criteria.